Justiça e liberdade: a dignidade da pessoa humana e o equilíbrio social - Tucunduva, Ricardo Cardozo de Mello (2014)
perspective, mainly due to the role he assumed as a social balance factor from the process of redemocratization of Brazil, which occurred in the second half of the last century, after nearly thirty years of military government. The path taken by the Brazilian nation in search of Democracy led to the convocation of a National Constituent Assembly, whose work resulted in the Constitution of the Federative Republic of Brazil, from October 5, 1988. With the new Charter - called Citizen Constitution - the dignity of the human person not only gained the status of a constitutional principle, but as one of the foundation of the Republic, and this is a significant change, with deep and eternal reflections in the national life. This swerve and the special distinction that gives the protection to the rights of the human person, are consequences of what scholars call the "pendulum movement of History", which means, the natural and inexorable change of values prevailing in a certain society, from time to time, from one extreme to another, given that the social life is dynamic and the human being is always in search of a better way to live. But since past almost three decades, although already breathing democratic airs, Brazil continues to pursue the dream of social balance, and the solution to the existing disagreement, which embarrass the fluidity of social relations, pass, of course, through the correct interpretation that gives the scope of constitutional and infra-constitutional devices that incorporate the Brazilian legal system. Thus, already sees the importance of the theme. The paper is divided into three parts and, primarily, seeks to identify the theoretical premises that lay the foundation of the study, starting from a hypothetical deductive methodology with the objective to build substrate for a better understanding of the thesis. It is the Science of Law that gives focus to the paper, but interdisciplinary references are used, notably of History, Philosophy and Political Science. The final conclusions can be summarized in the following statement: The Principle of Human Dignity, in a wide perspective of equality, succors one who violates the Penal Law, have to succor each offended by this violation, under penalty of the commitment of the maintenance of social equilibrium , which reflects a critical to the leniency that, in Brazil, the delinquents are being treated